Adherence to the Mediterranean Diet and Its Association With Sleep Quality and Chronotype Among Youth: A Cross-Sectional Study - Naja, Farah; Hasan, Hayder; Khadem, Safiya Hassan; Buanq, Maryam Ahmed; Al-Mulla, Haya Khalid; Aljassmi, Aysha Khalifa; Faris, MoezAlIslam Ezzat (Frontiers in Nutrition, 2022)
Background: Evidence indicates that many university students have poor adherence to a healthy diet accompanied by unhealthy lifestyle behaviors. Chrono-nutrition is an emerging field of research that examines the pattern of optimum daily activity in relation to the human’s dietary patterns, and their reflections of variable health indicators such as sleep quality. However, there is a scarcity of research that examines the relationship between adherence to the healthy eating pattern, like the Mediterranean diet (MD), with sleep quality and chronotype among university students. Methods: A cross-sectional study was conducted, and convenience sampling was used. Participants were assessed for adherence to the MD using the Mediterranean Diet Quality Index (KIDMED), for sleep quality using the Pittsburgh Sleep Quality Index (PSQI), and for chronotype using the Morningness-Eveningness questionnaire (MEQ). Results: The study included 503 university students, most of them (81.5%) were females. Only 15.1% and 16.9% reported morningness chronotype and good sleep quality, respectively. About half of the students showed medium and high adherence to the KIMED. In-depth analysis revealed that students with good adherence to the MD were more likely to have a good sleep quality (OR=0.35; 95%CI: 0.21-0.59; P<0.001) even after adjustment for age and sex (OR=0.36; 95%CI: 0.21-0.62; P<0.001). The regression analysis also showed that those with good adherence to the MD had a significant association with better subjective sleep quality, less sleep latency, sleep disturbance, and daytime dysfunction even after adjustment for age and sex. Those with morningness chronotype had about a 6-fold higher chance to have good adherence to the MD (OR=5.67; 95%CI: 2.86-11.26; P<0.001 respectively). Conclusions: Good adherence to the healthy diet presented in the MD among university students is associated with morningness chronotype and with improved overall sleep quality and sleep components. Long-term, controlled intervention research works are warranted for more elaboration on the impact of chronotype and dietary habits on sleep quality and other important aspects such as mental health and academic achievement.